Pengembangan Usaha Sablon Kaos Kustom Nyala Tshirt Berbasis Digital dan Ramah Lingkungan untuk menumbuhkan Jiwa Kewirausahaan Mahasiswa - Yuliati, Yuliati; Indriyatni, Lies; Mutiarasari, Anggun; Isnain, Ariyantiano Bagus Muchamad; Jannah, Diah Riyadlil; Saudah, Nurus (STIE Pelita Nusantara, 2024)
The clothing industry, particularly t-shirts, has experienced rapid growth as a means of self-expression and lifestyle in recent decades. The demand for custom t-shirts has increased alongside society's interest in unique and personalized clothing. Digital technology and printing have facilitated the rapid and high-quality production of custom t-shirts. Custom t-shirt printing businesses offer promising business opportunities by understanding market trends, consumer needs, and utilizing the latest technology.